Bodově podepřená železobetonová deska - Marčanová, Martina (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Cílem bakalářské práce je navrhnout vybrané konstrukce vícepodlažního obchodního domu. Nosnou konstrukci tvoří monolitický železobetonový skelet. Pro práci byla vybrána železobetonová lokálně podepřená stropní deska nad nejnižším patrem, vnitřní sloup, základová patka a montované železobetonové schodiště.

The aim of the bachelor thesis is to design selected structures of the multi-storey department store. The supporting structure is a cast in place reinforced concrete frame. A reinforced concrete flat above the lowest floors, an inner column, a foundation pad and a prefabricated reinforced concrete staircase were selected for the work.
Reinforced concrete flat
Keywords: Železobetonová monolitická konstrukce; obchodní centrum; lokálně podepřená stropní konstrukce; sloup; základová patka; prefabrikované schodiště.; Cast-in-place reinforced concrete structure; office building; locally supported floor slab; column; foundation pad; wall; precast staircase.